A CROSS-SECTIONAL STUDY TO ASSESS THE PHYSICAL FITNESS INDEX IN MEDICAL STUDENTS - DR.T.Hari Prasad; DR. Thyelnai Dawn Khaling; DR.B.V. SURENDRA (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
BACKGROUND: The physical fitness index assesses both physical fitness for muscular work and capacity to recover from it. The Harvard Step Test (HST) examines an individual’s physical fitness. The present study was conducted to find the physical fitness Index of MBBS students using the Harvard step test and to compare the physical fitness between male and female medical students MATERIALS AND METHODS: The present cross-sectional Study was conducted in the Department of Physiology, Viswabharathi Medical College, Kurnool. The subjects selected for this study were first year medical students admitted for first MBBS course and physical fitness index was measured using Modified Harvard Step test and physical fitness was compared between male and female medical students. Data was analysed using SPSS version 21. RESULTS: For 100 students, interpretation of the PFI scores was found to be poor for 57%, low average for 4%, average for 6%, good for 22%, and excellent for 11% of students. Among male participants, distribution of poor, low average, average, good, and excellent PFI was 46%, 4%, 8%, 26% & 17% respectively. Among female participants, distribution of poor, low average, high average, good, and excellent PFI was 68%, 4%, 4%, 18%, and 6% respectively. CONCLUSION: This study concluded that medical students lacked adequate levels of physical fitness, whereas male students were more physically fit than female students. Academic curriculum should include and aggressively concentrate on students’ physical exercise, encouraging them to incorporate a healthy lifestyle into their everyday routines. If adopted, it might dramatically reduce the burden of noncommunicable illnesses in the future.